ANALISIS POSITIONING KERIPIK KENTANG DENGAN PENDEKATAN METODE MULTI DIMENSIONAL SCALLING DI KOTA BATU - Siti Asmaul Mustaniroh; Aunur Rofiq Mulyarto; Siti Nurkhasanah (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
Potato chips are one of the main products of Batu city. Based on data from Batu government’s in 2002, there are only 2 selling units. In 2008, amount of potato chips and another selling unit, so the research on positioning of potato chips in Batu city is important to do. The purpose of this research are to understand which attributes which influence custumer consideration to buy and to consume potato chips, and to analyze positioning which is formed between four potato chips brand (Cita Mandiri, Gizi Food, Leo, Rimbaku) based on costumer perception in Batu city by using Multi Dimensional Scaling method. Attributes that influence costumer to buy and to consume potato chips are product (taste and crunchy level), price (product price compare with quality, and considerable price products), distribution (the local stock of the products or how strategic is the selling location), promotion (the using of advertising or promotion media (such as internet, radio, or brochure)). Based on the Multi Dimensional Scaling Method, positioning follow this structure are Gizi Food as market leader, Leo as market challenger, and Rimbaku and Cita Mandiri as market follower.